Determinants of Transmigrant Households’ Income in Settlement Unit 3 Pagar Banyu, Ulu Talo District, Seluma Regency - Karimah, Miftahul; Istiqomah; Wibowo, Arif Andri (Research and Development Agency Ministry of Home Affairs, 2022)
In Indonesia, which consists of thousands of islands, it is very likely that there will be population inequality between islands. The government initiated the transmigration program to collectively encourage a more even distribution of the population, especially outside Java. The condition of the transmigration location with agricultural potential has encouraged most of the transmigrants to have their main livelihood as farmers. One of the transmigration destinations in Indonesia is Bengkulu Province, which is spread over eight regencies, but Seluma Regency is the only district that is included in the 3T (Frontier, Isolated, Underdeveloped) in Bengkulu Province which is allocated for the settlement of transmigrants, and the Settlement Unit 3 Pagar Banyu is one of the transmigration destinations since 2007. This study aims to analyze the effect of farm diversification, land size, family labor, and non-farm income on transmigrant household income. The population in this study consists of 50 transmigrant households in the settlement unit 03 Pagar Banyu, Ulu Talo District, Seluma Regency, all selected as respondents. Data were collected through interviews based on questionnaires, which were then analyzed with multiple linear regression. The results of this study indicate that farm diversification, land size, family labor, and non-farm income have a positive and significant effect on the income of transmigrant households. The results imply that transmigrant households should optimize farming in terms of diversification, land size, use of family labor, and engagement in non-farm income opportunities to increase income. Furthermore, the government should provide policies that focus on developing transmigrant farming.